Literature Review: Faktor-Faktor Penyebab Kejadian Rehospitalisasi Pada Pasien Congestive Heart Failure (CHF) - Kylalona, Gracylia; Suri, Nurma; Aulia Ramdini, Dwi; Sukohar, Asep (CV. Jasa Sukses Abadi, 2024)
Congestive Heart Failure (CHF) is a health disorder with a poor prognosis due to functional or structural heart defects that interfere with ventricular filling or blood ejection into the systemic circulation. CHF remains a significant global health concern with high rates of morbidity and mortality. The number of diagnosed CHF leading to frequent rehospitalization or re-admission due to symptom recurrence. Patients who experience readmitted to the hospital after initial admission have a risk of mortality, with about 50% dying within 6 months and 25-35% passing away within 12. In this review focuses on exploring the factors contributing to rehospitalization among CHF patients. The methodolgy involved analyzing electronic database for relevant studies published over the past decade. Factors identified as leading to rehospitalization in CHF patients include a history of hypertension, non-compliance with taking medication, and an unhealthy lifestyle. Pharmacists play an important role in providing education to patients and helping to fulfill patient medication compliance.